2017
DOI: 10.1051/bmdcn/2017070201
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and its link to type II diabetes mellitus

Abstract: Autophagy, a double-edged sword for cell survival, is the research object on 2016 Nobel Prize in Physiology or Medicine. Autophagy is a molecular mechanism for maintaining cellular physiology and promoting survival. Defects in autophagy lead to the etiology of many diseases, including diabetes mellitus (DM), cancer, neurodegeneration, infection disease and aging. DM is a metabolic and chronic disorder and has a higher prevalence in the world as well as in Taiwan. The character of diabetes mellitus is hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 184 publications
1
70
0
1
Order By: Relevance
“…Autophagy regulates the function of insulin‐sensitive tissues such as skeletal muscle, liver, visceral fat, and subcutaneous fat, as well as islet β cells (Yang et al, ), while deficient autophagy will lead to the impairment of islet β‐cell function and mass, thus eventually leading to the incidence of diabetes (Marrif & Al‐Sunousi, ). Several signal pathways involving in the regulation of autophagy, such as AMPK/mTOR signal pathway, have been confirmed to play an important role in protecting islet β cells (Varshney, Gupta, & Roy, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy regulates the function of insulin‐sensitive tissues such as skeletal muscle, liver, visceral fat, and subcutaneous fat, as well as islet β cells (Yang et al, ), while deficient autophagy will lead to the impairment of islet β‐cell function and mass, thus eventually leading to the incidence of diabetes (Marrif & Al‐Sunousi, ). Several signal pathways involving in the regulation of autophagy, such as AMPK/mTOR signal pathway, have been confirmed to play an important role in protecting islet β cells (Varshney, Gupta, & Roy, ).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a highly conserved process to eliminate aged and miss‐folded proteins or damaged organelles for maintaining cellular homeostasis and promoting cell survival (Levine & Kroemer, ,; Zhang & Chen, ). The dysfunction of autophagy may induce a series of diseases, such as diabetes mellitus, cancer, aging‐related diseases, and neurodegenerative diseases (Chen & Karantza, ; Chen & Karantza‐Wadsworth, ; Fan et al, ; Kou & Chen, ; Yang et al, ). Deficient function of islet β cells is a major pathological features of diabetes mellitus, but autophagy plays an important role in regulating the structure and functions of β cells through clearing senescent cells and damaged proteins or organelles, and protecting islet β cells against apoptosis (Las & Shirihai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of tumor cell apoptosis is one of the best strategies for treating glioma and multiple types of cancers (27,28). Apoptotic death can be activated by three main pathways (17,29). The extrinsic pathway is triggered through binding of extrinsic signals to death receptors, which leads to activation of caspase-8 (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic death can be activated by three main pathways (17,29). The extrinsic pathway is triggered through binding of extrinsic signals to death receptors, which leads to activation of caspase-8 (29,30). The mitochondrial (intrinsic signaling) pathway is activated upon cellular stresses such as ROS production and ΔΨm disruption, and this results in activation of caspase-9.…”
Section: Discussionmentioning
confidence: 99%
“…Documents reported that autophagy was wildly involved in variety of human diseases, such as cancer, inflammatory diseases, Parkinson disease, cardiovascular Disease, diabetes mellitus [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%